Legal Protection for the Weaker Party in Standard Form Contracts Based on Balance in Indonesian Civil Law - Agus Widyantoro (Indonesian Civil Law Review, 2026)
This study analyzes legal protection for weaker parties in standard form contracts based on the principle of balance in Indonesian civil law. The main issue arises because standard contracts are drafted unilaterally by business actors, so the resulting consent is merely formal and does not reflect equal bargaining positions. This research aims to examine the legal status of standard contracts, identify forms of imbalance in contractual clauses, and formulate dispute resolution mechanisms based on the principle of balance. The method used is normative legal research employing statutory, conceptual, and case approaches through library research of legislation, doctrine, and judicial practice. The results show that standard contracts remain valid agreements, but their binding force is not absolute because they are subject to the principles of good faith and propriety. Imbalance appears through exoneration clauses, unilateral modification, limitation of legal remedies, transfer of liability, and non-transparent drafting. Dispute resolution is not carried out through total annulment but through corrective interpretation, exclusion of unfair clauses, and adjustment of the parties’ obligations. This study confirms that the principle of balance functions as a corrective to freedom of contract so that contracts not only ensure legal certainty but also deliver substantive justice to weaker parties in modern contractual relationships.